Laser-induced non-linear light scattering in a suspension of black-body particles - Zelensky, S.E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
Characteristics of non-linear scattering of powerful pulses of Q-switched YAG:Nd³⁺ laser in an aqueous suspension of submicron-sized black-body particles has been investigated. Proposed is a model describing the results of experiments. This model involves laser-induced overheating of suspended particles and vaporization of surrounding water with subsequent rapid growth of vapor shells around the particles.